A brincadeira da cultura tradicional da infância na formação musical do pedagogo - Traverzim, Monique [UNESP] (2015)
This research aims to show that it is possible to Educator, without specific training in Music, take responsibility for Music Education classes in Basic Education, specifically in kindergarten and elementary school. It is a qualitative research and the data collection was made using: a) questionnaires, b) experience reports, and c) a participant observation of a Research Seminar, which was prepared by the researcher, based on Play of Traditional Culture of Childhood. According to General Systems Theory and Culture of Childhood, our premise was that the human being is a 'playing' being; what was ratified when observing that, when the teacher is playing, there is no prejudice about self-production in music making, and also that these teachers feel able to conduct a musicalization class with their students. From the class teachers results concerning to the: 1) participation, 2) involvement, 3) dedication during the course of the seminar, and 4) the actions they have developed in schools where they operate; we inferred that they can carry on what the new Brazilian legislation demands about teaching Music with Children's Play. We hope that, with this research, it is possible to contribute to the Pedagogy professionals, specially, if it: 1) increases their confidence in approaching to the music, 2) assists them in Music teacher training, and 3) collaborates with elements for further work on the subject